2023
DOI: 10.1155/2023/9293505
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Keratin Hydrolysate Extraction from Tannery Sheep Hair Waste

Abstract: Tannery hair wastes are becoming a challenge for tanners regarding environmental pollution control and human health. In this study, an experiment had been designed to hydrolyse sheep hair in an alkaline medium, and the operational condition for the alkaline extraction of KH has been modeled and optimized. The structure, morphology, functional groups, particle size, and molecular mass of the KH extracts were evaluated experimentally by scanning electron microscopy, X-ray diffraction, Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This indicates that the experimental extract has relatively less hazardous inorganic oxides and salinity compared with most commercial retanning agents and the higher ash percentage indicates an excessive amount of the hydrolyzing agent employed. The findings suggests that the lesser ash contents are more likely to be green because ash content is a key feature of any retanning agents manufactured and employed in the leather manufacturing [ 40 ]. Furthermore, one of the biggest issues facing the tanning industry is the treatment of wastewater containing a high salt load.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the experimental extract has relatively less hazardous inorganic oxides and salinity compared with most commercial retanning agents and the higher ash percentage indicates an excessive amount of the hydrolyzing agent employed. The findings suggests that the lesser ash contents are more likely to be green because ash content is a key feature of any retanning agents manufactured and employed in the leather manufacturing [ 40 ]. Furthermore, one of the biggest issues facing the tanning industry is the treatment of wastewater containing a high salt load.…”
Section: Resultsmentioning
confidence: 99%
“…The extracted keratin has been used for a wide range of applications, such as for fertilizer industries [ 27 ]; for industries producing animal feeds [ 28 , 29 ]; as a biomaterial for example, for the production of keratin-based bioplastic films from chicken feathers [ 21 , 30 , 31 ]; as a biomedical material using sodium sulfide-based extraction [ 32 ]; as an industrial application of tannery wastewater treatment to adsorb chromium [ 12 , 33 ]; and as a replacement for salt in textile processing to enhance dyestuff uptake [ 26 , 34 ]. Therefore, many keratin sources, including waste chicken feathers, wool waste from the textile and wool processing industries, hog hair, horn meal, hoofs, nails and tannery hair waste, have been used for the extraction of keratin hydrolysate [ 27 , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. It is slowly becoming more common to produce biobased retanning and chrome exhaust aids, as well as use them in the production of leather.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the rate of protein solubilization is directly proportional to the hydrolyzing agent concentration and temperature when keratin is extracted from sheep’s hair. The types and numbers of bonds in the polypeptide are primarily connected to the optimum parameters, which were discovered to be 80 °C, 0.5 N, and 3.5 h. The protein’s sulphide link is easily broken by temperature, allowing the protein to disintegrate ( Mengistu, Angassa & Tessema, 2023 ). In other reports, the yield percentage and absorption of extracted keratin in hydrolysate increase in response to change in the extraction time, NaOH concentration, and pH ( Teklemedhin, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still higher than the keratin yield from sheep hair hydrolyzed with Br ions at 100°C and sheep hair hydrolyzed with choline thioglycolate at 130 °C 38 (Table 1). This is attributed to the influence of the temperature used during hydrolysis 36,39 . Keratin precipitation occurs due to the addition of HCL.…”
Section: Separation and Precipitation Of Hydrolysate Samples From She...mentioning
confidence: 99%
“…These are rich in cysteine and contain fewer amounts of hydroxyproline and proline amino acids. However, β-keratins are present in the hard tissue protein of bird feathers, fish scales, nails, and others 8 .…”
Section: Introductionmentioning
confidence: 99%